The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00586-013-2737-1
|View full text |Cite
|
Sign up to set email alerts
|

Laminarthrectomy as a surgical approach for decompressing the spinal canal: assessment of preoperative versus postoperative dural sac cross-sectional areal (DSCSA)

Abstract: In this study, the clinical results of laminarthrectomy were good, and comparable with other reports for LSS. The rates of complications are also comparable with other reports in spinal surgery. A significant increase in the spinal canal diameter was achieved. Within the limitations a retrospective study gives, we conclude that laminarthrectomy seems to be a safe and effective surgical approach for significant decompressing the adult central spinal canal, and measurement of DSCSA, before and after surgery seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…In our study the rate of complications associated with lumbar microdecompression was lower than what has recently been reported for laminectomy and laminarthrectomy for spinal stenosis [20,21]. Smokers did not experience more complications or adverse events compared to nonsmokers in our study, possibly reflecting the minimally invasive nature of the procedure with small incisions, less muscle trauma and practically no need for bone healing.…”
Section: Discussioncontrasting
confidence: 73%
“…In our study the rate of complications associated with lumbar microdecompression was lower than what has recently been reported for laminectomy and laminarthrectomy for spinal stenosis [20,21]. Smokers did not experience more complications or adverse events compared to nonsmokers in our study, possibly reflecting the minimally invasive nature of the procedure with small incisions, less muscle trauma and practically no need for bone healing.…”
Section: Discussioncontrasting
confidence: 73%
“…Unlike the poor correlation between preoperative DSCSA and clinical symptoms documented in previous articles, serial change of DSCSA after decompression and clinical symptom showed significant correlation in these articles. Hermansem et al reported a significant correlation between the expansion ratio of DSCSA and the patient self reported effect of surgery after laminarthrectomy for DLSS (Pearson -3.71; p=0.006) 6) . Yamazaki et al performed prospective study to evaluate the serial changes in clinical result and DSCSA on MRI after bilateral fenestration 22) .…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports in the literature on serial changes of DSCSA after posterior decompression for DLSS 6 , 12 , 22) . Hiriki et al measured DSCSA preoperatively and in the early and late phases after various type of lumbar decompression surgery 12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DSCA evaluation has been suggested as a method to assess the compression (before surgery) and decompression (after surgery) of the dural sac by measuring the area of the spinal canal on pre-operative and post-operative imaging. [ 2 17 18 19 20 21 ] Actually, an increase of the DSCSA has been described as positively correlated to a better functional outcome,[ 31 ] but the postoperative nature of this measurements limits its clinical relevance. [ 22 ] Collectively, these data suggest that no other imaging methodologies apart from preoperative and postoperative CT/MRI scans have been identified so far to assess the compression and the decompression of the spinal canal after surgery for lumbar degenerative stenosis.…”
Section: Discussionmentioning
confidence: 99%